2004
DOI: 10.1117/1.1648646
|View full text |Cite
|
Sign up to set email alerts
|

Imaging wound healing using optical coherence tomography and multiphoton microscopy in an in vitro skin-equivalent tissue model

Abstract: Laser thermal injury and subsequent wound healing in organotypic, skin-equivalent tissue models were monitored using optical coherence tomography (OCT), multiphoton microscopy (MPM), and histopathology. The in vitro skin-equivalent raft tissue model was composed of dermis with type I collagen and fibroblast cells and epidermis of differentiated keratinocytes. Noninvasive optical imaging techniques were used for time-dependent, serial measurements of matrix destruction and reconstruction and compared with histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 20 publications
1
93
0
Order By: Relevance
“…Developments will need to include faster data acquisition and processing for in vivo real-time recording and enhancement of resolution by use of broad-band light sources, OCT-multiphoton microscopy, or polarization-sensitive OCT (18). Inevitably, such developments will need to be finely balanced against constraints placed by the particular in vivo milieu in which OCT is being used and the complex tissue profile.…”
Section: Discussionmentioning
confidence: 99%
“…Developments will need to include faster data acquisition and processing for in vivo real-time recording and enhancement of resolution by use of broad-band light sources, OCT-multiphoton microscopy, or polarization-sensitive OCT (18). Inevitably, such developments will need to be finely balanced against constraints placed by the particular in vivo milieu in which OCT is being used and the complex tissue profile.…”
Section: Discussionmentioning
confidence: 99%
“…This technique added contrast and enhanced the resolution of OCT due to the strong dependence of SHG on molecular and tissue structures. In the same year, Yeh et al 187 combined OCT with a superluminescent diode centered at 1310 nm and MPM with an ultrafast Ti:sapphire laser (150 fs, 800 nm) in two separate systems and compared it with histopathology to monitor laser thermal injury and subsequent wound healing in organotypic, skin-equivalent tissue models. The in vitro skin-equivalent rat tissue model was composed of dermis with type I collagen and fibroblast cells and epidermis of differentiated keratinocytes.…”
Section: Multimodal Oct and Mpmmentioning
confidence: 99%
“…In previous literature on skin burns assessment, OCT had mainly been used with a polarization sensitive setup for collagen imaging [36][37][38], but no measurement of the optical attenuation coefficient had been reported. However, other OCT studies found that low attenuation is correlated with low collagen content, in the case of agarose scaffolds [39] and ex vivo ovarian tissue [40], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%